2013
DOI: 10.1136/bmjopen-2012-002192
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory qualitative interview study about collaboration between medicine and dentistry in relation to diabetes management

Abstract: ObjectiveTo explore knowledge and attitudes regarding the links between diabetes and periodontitis of medical and dental healthcare professionals as well as those of people with diabetes.DesignQualitative interview study.Participants4 people with diabetes, four dental professionals, three general practitioners (GPs) with a specialist interest in diabetes, one GP without a specialist interest in diabetes, three diabetic nurse specialists and two consultant diabetologists.SettingPrimary and secondary care in New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
6
21
0
Order By: Relevance
“…Unfortunately, many patients with diabetes and also many medical clinicians are unaware of the links between periodontitis and diabetes, and of the potential benefits that periodontal treatment may have for diabetic patients. 42,43 Routine periodontal assessment should be performed in all patients, including those with diabetes. Ask the patient about their level of glycaemic control: many will be able to tell you their most recent HbA1c measurements.…”
Section: Implications For the Dental Professionalmentioning
confidence: 99%
“…Unfortunately, many patients with diabetes and also many medical clinicians are unaware of the links between periodontitis and diabetes, and of the potential benefits that periodontal treatment may have for diabetic patients. 42,43 Routine periodontal assessment should be performed in all patients, including those with diabetes. Ask the patient about their level of glycaemic control: many will be able to tell you their most recent HbA1c measurements.…”
Section: Implications For the Dental Professionalmentioning
confidence: 99%
“…Notwithstanding, this study found that the evidence for the bidirectional relationship between diabetes and periodontitis was valued by medical clinicians, and informing patients was considered legitimate by the medical team, particularly to the role of nurses [21]. As difficulties with collaborative working between dental and medical clinicians have been reported previously in the literature [22,23], and dissemination of guidelines alone is insufficient in promoting a change in clinical practice [24], this study aimed to explore potential ways to enable improved inter-professional working as outlined in extant diabetes and periodontitis guidance documents.…”
Section: Aap Americanmentioning
confidence: 58%
“…In addition to bacterial components (e.g., lipopolysaccharide or LPS), periodontal disease allows locally‐produced proinflammatory mediators (e.g., interleukin‐(IL‐1) 1β, tumor necrosis factor‐α (TNF‐α), IL‐6, and prostaglandin E2 (PGE2)) to pour into the bloodstream, initiating responses in more distant tissues (Gemmell, Marshall, & Seymour, ; Loos, ; Loos, Craandijk, Hoek, Wertheim‐van Dillen, & van der Velden, ; Moutsopoulos & Madianos, ). The dissemination of bacteria and their biproducts into the bloodstream have the added effect of inducing system‐level infection responses that may instigate or affect the progression of cardiovascular diseases (for reviews of the evidence, see Dietrich, Sharma, Walter, Weston, & Beck, ; Dietrich et al, ), chronic obstructive pulmonary disease (Liu et al, ; Wang et al, ; Zeng et al, ), pneumonia (Awano et al, ; El Attar, Zaghloul, & El Menoufy, ; Scannapieco & Mylotte, ; Sharma & Shamsuddin, ; Terpenning et al, ), and diabetes (Bissett, Stone, Rapley, & Preshaw, ; Borgnakke, Ylöstalo, Taylor, & Genco, ; Lalla et al, ; Nelson et al, ; Taylor, Burt, Becker, Genco, & Shlossman, ). For example, platelet aggregation can be induced by oral bacteria such as P. gingivalis and S. sanguis or by the proinflammatory immune cytokines generated in response to them, affecting the formation of thrombi in the arteries and veins (Herzberg & Meyer, ).…”
Section: Discussionmentioning
confidence: 99%